Evaluation Method of Water Hazard Control Effect of Coal Seam Floor in Deep Mining: Sequence Verification Evaluation - Yanbo Hu; Wenping Li; Qiqing Wang; Xinmin Chen; Gang Zheng (Geofluids)
Deep, highly pressurized aquifers seriously threaten the exploitation of resources of North China coalfield. At present, there is no particular guidance system to evaluate the prevention and control effect of water inrush disaster in deep coal seam mining. Therefore, this research focuses on the evaluation of the method for confined water disaster prevention and control effect of deep coal seam mining. Based upon various methods, such as effective thickness and water resistance capacity of aquifuge, water inrush coefficient, GIS (Geographic Information System) analysis of grouting data, dense drilling verification, and professional analysis system based on integrated sequence evaluation, the evaluation of the method for confined water disaster prevention and control effect of deep coal seam mining was put forward for the first time. The proposed method was called the “sequence verification evaluation (SVE)” method. The prevention and control of the effects of Ordovician water inrush disaster in deep mining of Huanghebei coalfield was evaluated using the proposed SVE method. The results show that the SVE method can effectively reflect the prevention and control of the effects of water inrush from confined water and provide scientific basis for the safe production of deep coal seam mining.